THE RELATIONSHIP BETWEEN TEACHERS’ ATTITUDES TO DISTANCE EDUCATION AND THEIR LIFE SATISFACTION - Arif KIRKIÃ‡, Kamil; YAHÅžÄ°, Ã–mer (MOJES: Malaysian Online Journal of Educational Sciences, 2021)
Teachers’ attitudes toward distance education are important in terms of the effectiveness of the distance education process. They become even more critical during this time of global pandemics when face-to-face education has been compulsorily replaced by distance education. The worldwide coronavirus pandemic has changed the practices of the teaching profession. This period has revealed how teachers’ life satisfaction while carrying out their profession can be affected by changes in education delivery. The aim of this study is to examine the relationship between teachers’ attitudes toward distance education and their life satisfaction during the distance education process. This research used the correlational survey method, a method in quantitative research. The sample group consisted of teachers (1,233 male and 3,671 female educators) working in different branches in Izmir. The "Life Satisfaction Scale" and "Attitude toward Distance Education Scale" were applied. Participants’ demographic information was obtained using a "Personal Information Form" designed by the researchers. According to the results of the study, while there is a notable difference in teachers’ limitations toward distance education and life satisfaction according to gender, there is no difference in the advantages gained from and attitudes toward distance education.